HER2 recruits AKT1 to disrupt STING signalling and suppress antiviral defence and antitumour immunity - Wu, Shiying; Zhang, Qian; Zhang, Fei; Meng, Fansen; Liu, Shengduo; Zhou, Ruyuan; Wu, Qingzhe; Li, Xinran; Shen, Li; Huang, Jun; Qin, Jun; Ouyang, Songying; et al. (Nature cell biology, 2019)
Sensing cytosolic DNA through the cGAS–STING pathway constitutes a widespread innate immune mechanism to monitor cellular damage and microbial invasion. Evading this surveillance is crucial in tumorigenesis, but the process remains largely unexplored. Here, we show that the receptor tyrosine kinase HER2 (also known as ErbB-2 or Neu) potently inhibits cGAS–STING signalling and prevents cancer cells from producing cytokines, entering senescence and undergoing apoptosis. HER2, but not EGFR, associates strongly with STING and recruits AKT1 (also known as PKB) to directly phosphorylate TBK1, which prevents the TBK1–STING association and TBK1 K63-linked ubiquitination, thus attenuating STING signalling. Unexpectedly, we observed that DNA sensing robustly activates the HER2–AKT1 axis, resulting in negative feedback. Accordingly, genetic or pharmacological targeting of the HER2–AKT1 cascade augments damage-induced cellular senescence and apoptosis, and enhances STING-mediated antiviral and antitumour immunity. Thus, our findings reveal a critical function of the oncogenic pathway in innate immune regulation and unexpectedly connect HER2–AKT1 signalling to the surveillance of cellular damage and antitumour immunity. Wu et al. demonstrate that HER2 recruits AKT1 to disrupt the STING signalosome, thereby suppressing damage-induced cellular senescence and STING-mediated antiviral and antitumour responses in vivo.